The Influence of Kotanopan Muslim Community Perceptions on Financing Decisions at BPRS Sidanglaya in Mandailing Natal Regency North Sumatra - Nurul Fadilah; Atika; Muhammad Arif (Jurnal Investasi Islam, 2026)
This study aims to analyze the influence of Kotanopan Muslim community perceptions on financing decisions at BPRS Sidanglaya in Mandailing Natal Regency, North Sumatra. The research method used is a quantitative approach with purposive sampling techniques involving 83 respondents from the Kotanopan Muslim community who are financing customers at BPRS Sidanglaya. Data collection was conducted through the distribution of questionnaires, while data analysis used multiple linear regression with the help of the SPSS application. The results showed that partially, functional value, emotional value, and risk perception had a positive and significant effect on financing decisions. Meanwhile, religious value did not have a significant effect on financing decisions. Simultaneously, all independent variables had a significant effect on the decision to choose financing. These findings indicate that product benefits, emotional comfort, and risk perception play an important role in influencing the Muslim community's decision to choose financing products at BPRS Sidanglaya.